Revitalizace kabelážního systému v budově Hudební fakulty Janáčkovy akademie múzických umění v Brně - Špičák, Jan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Předmětem této bakalářské práce je provedení analýzy kabelážního systému v budově Hudební fakulty Janáčkovy akademie múzických umění v Brně a následný návrh na jeho vylepšení na úroveň, odpovídající současným standardům. Práce řeší trasování horizontální sekce a fyzickou topologii sítě, jsou uvedeny doporučené aktivní prvky včetně jejich doporučeného zapojení, uvedené konkrétní nově nakoupené vybavení však není striktně vyžadováno. V závěru se práce zabývá finančním zhodnocením návrhu, které je pro veřejnou instituci klíčové.

The objective of this bachelor’s thesis is to perform an analysis of structural cabling in the building of the Faculty of Music, Janáček Academy of Music and Performing Arts, and to propose an improvement of mentioned cabling system to achieve current industry standards of stability & reliability. Both horizontal cabling routes and physical network topology are taken into account; network hardware recommendation with its setting is also included, although mentioned newly purchased equipment is not strictly required. In the conclusion, the thesis deals with an economic evaluation of the proposed solution as a major decision-making factor for the chosen public institution.
Revision & improvement of structural cabling in the building of the Faculty of Music, Janáček Academy of Music and Performing Arts
Keywords: JAMU; Hudební fakulta; strukturovaná kabeláž; UTP cat. 6A; RJ-45; 10GE; singlemode; VoIP; L3 switch; PoE; VLAN; JAMU; Faculty of Music; structural cabling; UTP cat. 6A; RJ-45; 10GE; singlemode; VoIP; L3 switch; PoE; VLAN